PENINGKATAN HASIL BELAJAR IPS MENGGUNAKAN MAKE A MATCH KELAS III SDN 4 TELUK SUAK BENGKAYANG - Surianto, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: This study aimed to describe the learning outcome of students in the learning of Social Sciences by using Make a Match in class III State Elementary School 4Teluk Suak Bengkayang. The research method used is descriptive. Form of research is classroom action research. The sample was 20 students. Data were analyzed using direct observation. Data collector is observation sheet teachers in implementing the learning ability and pieces of learning outcomes of students. This research was conducted three cycles, with the result; (1) The ability of teachers to prepare lesson plan first cycle of 3.71, 3.86 second cycle, and the third cycle 3.86 increased 0.15 in the second cycle and keep 3.86 in third cycle. (2) The ability of teachers in implementing the learning first cycle of 3.07, 3.54 second cycle and the third cycle 3.85 increase 0.47 in the second cycle and 0.31 in the third cycle. (3) The results of study of students in the first cycle of 64.50, 76/50 in second cycle and the third cycle 90.00 increased by 12.00 in second CycleÂ  and 13.50 in third Cycle.Make a Match can improve learning outcomes of social science in grade III primary school 4 Teluk Suak Bengkayang. Keywords: Learning Outcomes, Social Science, Make a Match